Physical Education as a Character Formation in Paringin City Elementary School in the Modern Era - Irmayanti; Arie Rakhman; Akhmad Amirudin (Universitas Negeri Semarang, 2025)
This research seeks to explore the role of physical education in shaping students' character at Paringin City Elementary School in the contemporary era. The examined character encompasses elements of religiosity, honesty, tolerance, discipline, and responsibility. This research employs a quantitative descriptive approach using a survey technique, in which questionnaires are distributed to fifth-grade students across 10 elementary schools in Paringin City. The gathered data is analyzed using the percentage technique and presented through tables and bar charts to depict each category in the character development process.. The study results indicate that physical education significantly contributes to shaping students' character. The majority of the analyzed character aspects fall within the categories of